2013
DOI: 10.31989/ffhd.v3i6.54
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of 1, 25-dihydroxyvitamin D3 and soy protein extract (SPE) on oral cancer growth in vitro: evidence for potential functional relationships.

Abstract: Background: Previous studies have found specific soy isoflavones (Genistein, Daidzein, Glycitein) demonstrate anti-tumor properties against several cancer types, including oral cancer. Few studies have evaluated whole soy extract, containing a combination of these isoflavones and other bioreactive compounds, which may function synergistically and more effectively against oral cancers. Preliminary work by this group has now demonstrated whole soy protein extract (SPE) inhibits oral cancer cell growth specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Several in vitro studies on vitamin D showed consistent findings supporting its potential to inhibit SCC growth and OLP development, and enhance the therapeutic effect of additional cancer therapies [54,55]. In vivo animal studies further supported its effects in delaying cancer progression [43], but showed no significant effect on oral squamous cell carcinoma cell death rate.…”
Section: Discussionmentioning
confidence: 81%
“…Several in vitro studies on vitamin D showed consistent findings supporting its potential to inhibit SCC growth and OLP development, and enhance the therapeutic effect of additional cancer therapies [54,55]. In vivo animal studies further supported its effects in delaying cancer progression [43], but showed no significant effect on oral squamous cell carcinoma cell death rate.…”
Section: Discussionmentioning
confidence: 81%
“…Studies on the expression of genes associated with the phenomenon of apoptosis in oral squamous cell carcinoma cell lines (SCC15, SCC25, and CAL27) found that treatment with calcitriol at physiological concentrations (10-125 nmol/L) influenced programmed cell death by modulating the mRNA expression of key cell cycle and apoptotic signalling pathway regulators, such as p53, c-myc, ornithine decarboxylase (ODC), caspase-2, caspase-8, and Bax. The administration of calcitriol induced distinct dose-dependent, growth-inhibitory effects in all three oral cancer cell lines in vitro [174]. Furthermore, in KB cells from an oral floor squamous cell carcinoma, the mRNA of survivin, an inhibitor of apoptosis protein (IAP) family member, was clearly decreased by treatment with calcitriol.…”
Section: The Innate Immune Responsementioning
confidence: 97%